2013
DOI: 10.1007/s11414-013-9343-1
|View full text |Cite|
|
Sign up to set email alerts
|

A Cluster Randomized Trial of Adding Peer Specialists to Intensive Case Management Teams in the Veterans Health Administration

Abstract: Use of Peer Specialists (PSs)—individuals with serious mental illness who use their experiences to help others with serious mental illness—is increasing. However, their impact on patient outcomes has not been demonstrated definitively. This cluster randomized, controlled trial within the Veterans Health Administration compared patients served by three intensive case management teams that each deployed two PSs for one year, to the patients of three similar teams without PSs (Usual Care). All patients (PS group=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
119
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 56 publications
3
119
1
1
Order By: Relevance
“…Additionally, it is noted that trial methodology -especially the random allocation of people to receive peer support or not -can undermine the relationship at the heart of peer support (Corrigan and Salzer, 2003). To date, only a single cluster randomised controlled trial has been reported, comparing veterans' mental health services including peer workers as part of the staff team with those without (Chinman et al, 2015). This study showed a greater improvement in patient activation -measuring, for example, the extent to which patients know what their medication is for (Green et al, 2010) -in those services with peer workers compared to those without.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is noted that trial methodology -especially the random allocation of people to receive peer support or not -can undermine the relationship at the heart of peer support (Corrigan and Salzer, 2003). To date, only a single cluster randomised controlled trial has been reported, comparing veterans' mental health services including peer workers as part of the staff team with those without (Chinman et al, 2015). This study showed a greater improvement in patient activation -measuring, for example, the extent to which patients know what their medication is for (Green et al, 2010) -in those services with peer workers compared to those without.…”
mentioning
confidence: 99%
“…This study showed a greater improvement in patient activation -measuring, for example, the extent to which patients know what their medication is for (Green et al, 2010) -in those services with peer workers compared to those without. Authors note that it was difficult to attribute that difference to the peer component, with peers performing the same duties as other members of the team (Chinman et al, 2015). The reviews cited above also note a lack of reporting of what peers do, how that is distinctive from what other mental health workers do and how that might bring about change (Pitt et al, 2013;Lloyd-Evans et al, 2014).…”
mentioning
confidence: 99%
“…In the article by Chinman, Oberman, Hanusa, et al 5 in this issue of the Journal of Behavioral Health Services & Research (JBHS&R), we read about a cluster randomized, controlled trial that compared outcomes among veterans with serious mental illnesses who had substantial histories of inpatient care who were served either by intensive case management teams that deployed peer staff or by similar teams that had not yet hired peer staff. An innovative feature of this study was that it compared outcomes of all persons served by these teams rather than just those persons who were assigned peer staff, as has been done in most previous studies.…”
mentioning
confidence: 99%
“…Peers and clinicians have different skill sets and work responsibilities that could affect PAD facilitation rates and quality. The peer's role emphasizing empowerment and recovery may be a natural fit with PAD facilitation, because peers may be particularly able to help consumers achieve some recovery outcomes (13,14), serve as role models in recovery, and foster a person-centered process in successful PAD completion. On the other hand, clinicians' training may make it easier to formulate treatment preferences into clinically feasible and effective PADs.…”
Section: Resultsmentioning
confidence: 99%